Prática clínica no atendimento à síndrome de Asperger com diagnóstico tardio: uma proposta em psicologia sócio histórica - Camargo, Alberto José de (2015)
This paper is based on the report of a case of Asperger Syndrome (A.S.) with a late diagnosis and on some remarks on classic biomedical and clinical psychology assessment and treatment of the Asperger Syndrome. The therapist and also a researcher, transforms the assistance of A.S. based in a classic biomedical framework into a social - historical clinic psychology practice, related to the assumptions of Vigotsky s Works (1924) of Mediation and Proximal Developmental Zone (PDZ). The patient of this case study has extreme difficulties in interpersonal relationship, in affect expressions, and over all, extreme difficulties in starting affective affairs with girls, despite his very good performance in academic and professional tasks. Nevertheless, his difficulties use to lead him to unemploymente menace and to learning déficits in his academic life. He never dares to make any questions to his teachers and colleagues. Aiming diagnosis purposes of difficulties and not deseases, the therapist brings important changes in the classic clinical setting , making therapy in outside environment, by introducing the patient s family and community into the clinical work. This new framework of therapy has the purpose of bringing emotional and dramatical experiences of life to the clinical work, like Veresov (2004) assumptions of the relationship between learning and development in a dialectic way of qualitative steps as a result of intensive emotional and cognitive experiences. The expected effects are the development of new habilities and potentialities as a result of some kind of compensation from the Asperger patient s level of difficulties. Participation of family and community are fundamental to the therapy goals. Aiming new potentialities and development of new habilities for the patient s growing goals, the therapist made a list of steps related to his clinical new approach directed to another therapists: a) Diagnosis of difficulties and potentialities, instead of deseases diagnosis; b) Life story of the patient his family and community; c) Widening up the subjective universe; d) Widening up the therapist and researcher role; e) Multiple mediators proposal; f) Sistemic studies of the patient s contexto of life; g) Therpeutic actions directed toward the Human Rights